Quantifying Long‐Term and Event‐Scale Baseflow Effects across the Flood Frequency Curve. (25th June 2020) - Spellman, Patricia; Webster, Veronica
Abstract: Though metrics that quantify the long‐term water balance of a catchment have been known to influence the statistics of flood frequency data, little has been done to understand exactly what the substantive links are that causes baseflow to impact instantaneous annual maximum flows (IAMF). As abrupt changes to baseflow can occur via climate change and human disturbances, understanding the effects of baseflow on IAMF behavior can provide insight into how groundwater alterations and climate change can impact flood risk assessment, particularly for regional data aggregation. We thus seek to quantify baseflow impacts across the flood frequency curve considering a top down approach enumerating the differential impacts of baseflow (as Baseflow Index) across the IAMF flood frequency curve and then analyzing the impact of baseflow at the event‐scale. Results show that baseflow exerts significant influence over the entire flood frequency curve, showing a slight increase in effect with higher return period flows. At the event‐scale, the permeability of the catchment (proxied by baseflow rate during rising limb), significantly impacted the variability in IAMF and had more of an effect than antecedent moisture of the catchment (proxied by antecedent discharge). Furthermore, the effects of each of the event‐scale variables changed across climate regions and return periods, suggesting that changes to climate and groundwater abstractions would greatly affect the flood frequency curve. Abstract : Research Impact Statement : We use statistical models to quantify the impact of baseflow and antecedent moisture conditions on instantaneous annual maximum flows under long‐term and event‐based time scales.